2022
DOI: 10.3390/ijms23094542
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis and Identification of Drought-Responsive Genes of the CAMTA Gene Family in Wheat (Triticum aestivum L.)

Abstract: The calmodulin-binding transcription activator (CAMTA) is a Ca2+/CaM-mediated transcription factor (TF) that modulates plant stress responses and development. Although the investigations of CAMTAs in various organisms revealed a broad range of functions from sensory mechanisms to physiological activities in crops, little is known about the CAMTA family in wheat (Triticum aestivum L.). Here, we systematically analyzed phylogeny, gene expansion, conserved motifs, gene structure, cis-elements, chromosomal localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Phylogenetic analysis of amino acid sequences of P. edulis CAMTA , O. sativa CAMTA , Arabidopsis CAMTA , Z. mays CAMTA and B. distachyon CAMTA was performed, and we classified the amino acid sequences of PeCAMTAs into five subbranches (I~V) ( Fig. 1 ) according to Wang et al (2022) classification method, among which the protein sequences of Arabidopsis CAMTA genes were classified into one subclade, and the amino acid sequences of O. sativa , Z. mays and P. edulis CAMTA genes were grouped into one subclade. It is more closely related to O. sativa and Z. mays , and more distantly related to Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis of amino acid sequences of P. edulis CAMTA , O. sativa CAMTA , Arabidopsis CAMTA , Z. mays CAMTA and B. distachyon CAMTA was performed, and we classified the amino acid sequences of PeCAMTAs into five subbranches (I~V) ( Fig. 1 ) according to Wang et al (2022) classification method, among which the protein sequences of Arabidopsis CAMTA genes were classified into one subclade, and the amino acid sequences of O. sativa , Z. mays and P. edulis CAMTA genes were grouped into one subclade. It is more closely related to O. sativa and Z. mays , and more distantly related to Arabidopsis .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on wheat confirmed that the expression of TaCAMTA1a-B and TaCAMTA1b-B. A total of 1 was down- and up-regulated, respectively, in response to drought stress to maintain normal physiological functions associated with the plant, and wheat CAMTA gene family members also contain a large number of MYB elements ( Wang et al, 2022 ). The previous study also gave us ideas for subsequent stress experiments, and it became important to verify the expression of PeCAMTAs in response to drought stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High salinity induces changes in the expression of many stress-related genes [ 8 ]. Among these, various families of transcription factors (TFs) (e.g., NAC, AP2/ERF, MYB, WRKY, bZIP, bHLH and CAMTA) have been identified and characterized [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. The NAC TFs comprise one of the largest families of plant-specific TFs with 117 and 151 predicted members in Arabidopsis and rice [ 16 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…No duplication of TraesTM9SF genes in the wheat genome was recorded, and 177 TFs were 1 Introduction Wheat (T. aestivum) is an important food crop consumed worldwide (Ismagul et al, 2014). Diverse factors, including drought, salinity, nutrient limitation, pest attack, and extreme temperatures, can affect the growth, development, quality, and yield of wheat and other crops (Zhang et al, 2021;Ahlawat et al, 2022;Dissanayake et al, 2022;Fang et al, 2022a;Venzhik et al, 2022;Wang et al, 2022;Yue et al, 2022;Yu et al, 2022). It is essential to examine the mechanisms involved in wheat growth under such conditions to improve productivity; it is also vital to boost wheat growth under these conditions.…”
mentioning
confidence: 99%